PENERAPAN PERSONNEL DAN CULTURAL CONTROL UNTUK MENGATASI MASALAH MOTIVASI KERJA KARYAWAN PADA USAHA DAGANG “S” DI BONDOWOSO - Lavenia Rosalia; Ria Sandra Alimbudiono (CALYPTRA, 2018)
Abstrack - This study aims to evaluate personnel and cultural control to address employee motivation problems. This research specifically wants to know how the employee's motivation in a trading business in Bondowoso. Personnel and cultural control can influence informal control systems to overcome motivation problems. Informal control systems play a greater role in safeguarding human resources from misbehavior. The type of research used is applied research with qualitative approach method. This research tries to give recommendation to overcome the problem of work motivation of employees with the application of personnel and cultural control. This research is explanatory, by explaining how the role of personnel and cultural control that have been applied to the problem of work motivation contained in UD "S". The results of the study found three employee motivational problems that need to be addressed in the "S" Trade Business. Employee motivation occurs due to the weakness of informal corporate control system.